The Quality vs. the Quantity of Schooling: What Drives Economic Growth? (2011)
This paper challenges Hanushek and Woessmann's (2008) contention that the quality and not the quantity of schooling determines a nation's rate of economic growth. I first show that their statistical analysis is flawed. I then show that when a nation's average test scores and average schooling attainment are included in a national income model, both measures explain income differences, but schooling attainment has greater statistical significance. The high correlation between a nation's average schooling attainment, cumulative investment in schooling, and average tests scores indicates that average schooling attainment implicitly measures the quality as well as the quantity of schooling.